Penerapan Asas Terang dan Tunai dalam Jual Beli Hak Atas Tanah yang Hendak Dibatalkan Sepihak - Stella Defany Muslim; Fransiscus Xavierius Arsin (Jurnal Supremasi, 2023)
Agrarian Law or National Land Law in Indonesia adheres to Customary Law. One of them is the principle of cash and carry in the sale and purchase of land rights. People who have problems in the sale and purchase of land rights often want to cancel unilaterally without knowing about the application of the principle of cash and carry in the sale and purchase of land rights. This research method uses a form of normative legal research using a statutory approach with legal material collection techniques using literature studies and secondary data. The results of this study indicate that the carry principle of buying and selling land rights in Indonesia cannot be canceled unilaterally if it has fulfilled the cash and carry principles adopted by national land law from customary law in Indonesia.